The genetic diversity of D-loop sequences in eastern bent-winged bats (Miniopterus fuliginosus) living in Wakayama Prefecture, Japan - IIDA, Keisuke; KOBAYASHI, Ryosuke; HENGJAN, Yupadee; NAGATA, Nao; YONEMITSU, Kenzo; NUNOME, Mitsuo; KUWATA, Ryusei; SUZUKI, Kazuo; ICHIYANAGI, Kenji; MAEDA, Ken; OHMORI, Yasushige; HONDO, Eiichi (Journal of Veterinary Medical Science, 2017)
The eastern bent-winged bat (Miniopterus fuliginosus) is an insectivorous bat that lives in the caves, throughout Japan [11]. The bats aggregate in cave in populations of tens to thousands of individuals. We examined the mitochondrial D-loop sequences of bats in Wakayama, Japan, and divided them into 35 haplotypes. The sequences of 3 haplotypes in Wakayama were the same as those of 10 Miniopterus fuliginosus individuals living in China. Given the substitution rate of the D-loop region, we speculated that the bats had moved between Japan and China within the last 16,000 years. We could not determine how the bats crossed the sea; however, it is possible that the bats undergo dynamic movement widely throughout East Asia.